Surface Modification for the Collection and Identification of Fingerprints and Colorimetric Detection of Urea Nitrate. Issue 1 (25th July 2014) - Cross, Shoronia N.; Quinteros, Elliot; Roberts, Marcel
Abstract Glass surfaces were modified with a combination of dyes and reagents to allow for the potential simultaneous recording of a detailed fingerprint and the detection of the explosive urea nitrate (UN), as a proof of principle of surface modification for simultaneous linking of identity to manipulation of explosives. By coating microscope slides with 9, 10‐diphenylanthracene (DPA), p‐dimethylaminobenzaldehyde (p‐DMAB) and p‐dimethylaminocinnamaldehyde (p‐DMAC), a colorimetric change was observed in the presence of UN, while revealing a fingerprint with enough resolution to isolate at least 10 minutiae. This is the first step in creating point‐of‐care devices capable of detecting low concentrations of explosives and drug metabolites and connecting them to a fingerprint.